Bovine Model of Chronic Ischemic Cardiomyopathy: Implications for Ventricular Assist Device Research. Issue 12 (22nd July 2013) - Bartoli, Carlo R.; Sherwood, Leslie C.; Giridharan, Guruprasad A.; Slaughter, Mark S.; Wead, William B.; Prabhu, Sumanth D.; Koenig, Steven C.
Abstract: Ventricular assist devices (VADs) have emerged as a successful treatment option for advanced heart failure. The objective of this study was to develop a clinically relevant model of chronic ischemic cardiomyopathy to investigate functional, histological, and molecular changes during mechanical circulatory support. In calves (n = 17, 94 ± 7 kg), 90 μm microspheres were injected percutaneously into the left coronary artery. Serial echocardiography was performed weekly to evaluate cardiac function. Sixty days after coronary microembolization, a terminal study was performed via thoracotomy to measure hemodynamics. Regional myocardial and end‐organ blood flows were quantified with 15‐μm fluorescent‐labeled microspheres. Myocardial fibrosis, myocyte size, and myocardial apoptosis were quantified with histological stains. Eleven animals survived coronary microembolization and exhibited clinical and statistically significant echocardiographic and hemodynamic signs of severe systolic dysfunction. Statistically significant decreases in regional myocardial blood flow and increases in myocardial fibrosis, myocyte size, total myocardial apoptosis, and cardiac myocyte‐specific apoptosis were observed. End‐organ hypoperfusion was observed. Coronary microembolization induced stable and reproducible chronic left ventricular failure in calves. The anatomical size and physiology of the bovine heart and thorax are appropriate to study novel interventions for the clinical management of heart failure. This model is an appropriate physiological substrate in which to test VAD and adjunctive biological therapies.